2023
DOI: 10.1101/2023.10.17.562681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A purine salvage bottleneck leads to bacterial adenine cross-feeding

Ying-Chih Chuang,
Nicholas W. Haas,
Robert Pepin
et al.

Abstract: Diverse ecosystems host microbial relationships that are stabilized by nutrient cross-feeding. Cross-feeding can involve metabolites that should hold value for the producer. Externalization of such communally valuable metabolites is often unexpected and difficult to predict. Previously, we fortuitously discovered purine externalization by Rhodopseudomonas palustris by its ability to rescue growth of an Escherichia coli purine auxotroph. Here we found that an E. coli purine auxotroph can stably coexist with R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…1). A recent study showed that some strains of the purple sulfur bacterium Rhodopseudomonas palustris exude adenine when a bottleneck arises in its intracellular salvage due to low levels of the enzyme apt (30), highlighting a similar principle. In contrast, the pyrimidine thymidine, which unlike purines is not internally recycled (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). A recent study showed that some strains of the purple sulfur bacterium Rhodopseudomonas palustris exude adenine when a bottleneck arises in its intracellular salvage due to low levels of the enzyme apt (30), highlighting a similar principle. In contrast, the pyrimidine thymidine, which unlike purines is not internally recycled (Fig.…”
Section: Resultsmentioning
confidence: 99%